Editorial: refractory reflux sensitivity ‐ a place for baclofen?. Issue 4 (25th July 2022) - Katz, Philip O.
Abstract : LINKED CONTENT This article is linked to Pauwels et al papers. To view these articles, visit https://doi.org/10.1111/apt.17068 and https://doi.org/10.1111/apt.17129